2019
DOI: 10.3390/microorganisms7090333
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Assemblages in Pressurized Antarctic Brine Pockets (Tarn Flat, Northern Victoria Land): A Hotspot of Biodiversity and Activity

Abstract: Two distinct pressurized hypersaline brine pockets (named TF4 and TF5), separated by a thin ice layer, were detected below an ice-sealed Antarctic lake. Prokaryotic (bacterial and archaeal) diversity, abundances (including virus-like particles) and metabolic profiles were investigated by an integrated approach, including traditional and new-generation methods. Although similar diversity indices were computed for both Bacteria and Archaea, distinct bacterial and archaeal assemblages were observed. Bacteroidetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 116 publications
3
24
0
Order By: Relevance
“…Similarly to previous culture-independent results [ 13 , 31 ], even if (as it was expected) at different relative percentages and distribution, the cultivable bacterial community was composed by Proteobacteria (namely Gamma- and Alphaproteobacteria), Bacteroidetes (only in BC brines), Actinobacteria (mainly in TF) and Firmicutes, with most phylotypes that are well known for inhabiting cold and salty environments [ 64 , 65 , 66 ]. Most isolates from TSA 100 and TSA 50 plates were affiliated to Gammaproteobacteria and Actinobacteria.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Similarly to previous culture-independent results [ 13 , 31 ], even if (as it was expected) at different relative percentages and distribution, the cultivable bacterial community was composed by Proteobacteria (namely Gamma- and Alphaproteobacteria), Bacteroidetes (only in BC brines), Actinobacteria (mainly in TF) and Firmicutes, with most phylotypes that are well known for inhabiting cold and salty environments [ 64 , 65 , 66 ]. Most isolates from TSA 100 and TSA 50 plates were affiliated to Gammaproteobacteria and Actinobacteria.…”
Section: Discussionsupporting
confidence: 81%
“…Despite major advances have been made in the last decades, our current knowledge of physiology, metabolism, microbial ecology and interactions in cold-adapted microorganisms remains quite limited and it is particularly scarce with regard to less investigated habitats, such as Antarctic lake brines [ 56 ]. Brines of perennially ice-covered Antarctic lakes represent ideal environmental models to gain important insights on the ecology of the microbial life in Antarctica, by an overall synergistic analysis of both taxonomic diversity and functional capacities and interactions within a pristine ecosystem [ 13 , 57 ]. Recent culture-independent studies have shown that Antarctic brines in Boulder Clay and Tarn Flat lakes harbour diverse prokaryotic taxa, also highlighting astrobiological implications due to the strong similarities (e.g., harsh values of temperature and salinity) between these cryogenic habitats on Earth and other planetary and celestial bodies [ 13 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations